Insulin Is a Key Modulator of Fetoplacental Endothelium Metabolic Disturbances in Gestational Diabetes Mellitus - Sobrevia, Luis; Salsoso, Rocío; Fuenzalida, Bárbara; Barros, Eric; Toledo, Lilian; Silva, Luis; Pizarro, Carolina; Subiabre, Mario; Villalobos, Roberto; Araos, Joaquín; Toledo, Fernando; González, Marcelo; et al. (Frontiers in Physiology, 2016)
Gestational diabetes mellitus (GDM) is a disease of the mother that associates with altered fetoplacental vascular function. GDM–associated maternal hyperglycaemia result in fetal hyperglycaemia, a condition that leads to fetal hyperinsulinemia and altered L-arginine transport and synthesis of nitric oxide, i.e., endothelial dysfunction. These alterations in the fetoplacental endothelial function are present in women with GDM that were under diet or insulin therapy. Since these women and their newborn show normal glycaemia at term, other factors or conditions could be altered and/or not resolved by restoring a normal level of circulating D-glucose. GDM associates with metabolic disturbances, such as abnormal handling of the locally released vasodilator adenosine, and biosynthesis and metabolism of cholesterol lipoproteins, or metabolic diseases resulting in endoplasmic reticulum stress and altered angiogenesis. Insulin acts as a potent modulator of all these phenomena under normal conditions as reported in primary cultures of cells obtained from the human placenta; however, GDM and the role of insulin regarding these alterations in this disease are poorly understood. This review focuses on the potential link between insulin and endoplasmic reticulum stress, hypercholesterolemia, and angiogenesis in GDM in the human fetoplacental vasculature. Based in reports in primary culture placental endothelium we propose that insulin is a factor restoring endothelial function in GDM by reversing ERS, hypercholesterolaemia and angiogenesis to a physiological state involving insulin activation of insulin receptor isoforms and adenosine receptors and metabolism in the human placenta from GDM pregnancies.